Effect of Social Support and Self Efficacy on Drug Taking Adherence in Hypertensive Patients: A Meta-Analysis - Sukma Sukma; Didik Tamtomo; Argyo Demartoto (Masters Program in Public Health, 2023)
Background: Hypertension is a condition that causes a person to experience a drastic rise in blood pressure. Social support and self-efficacy are needed to improve skills, self-confidence and a sense of security for patients to be more compliant with taking medication. This study aimed to analyze the effect of social support and self-efficacy on medication adherence in hypertensive patients.Subjects and Method: This study is a meta-analysis using PICO, namely population: hypertensive patients; Intervention: good social support, good self-efficacy; Comparison: low social support, low self-efficacy; Result: medication adherence. The articles used in this study were obtained from two databases, namely PubMed and Google Scholar. Keywords in the article search “social cognitive theory (SCT)” AND “self efficacy“ AND ”social support “AND” hypertension” AND “medication adhe-rence”, cross-sectional. The included article is full English with a cross-sectional study design for 2012–2022 and reports the adjusted odds ratio (aOR) in multivariate analysis. Selection of articles using the PRISMA flowchart. Article analysis using the Review Manager 5.3 application.Results: 7 articles with a cross-sectional study involving 708 people with hypertension from 2 conti-nents namely Asia and Africa for systematic review and meta-analysis. The data collected showed that hypertensive patients with strong social support were twice as likely to adhere to medication as hypertensive patients with weak social support (aOR= 2.16; 95%CI= 1.82 to 2.57; p <0.001), Hyper-tensive patients with self-efficacy Those who are strong are more likely to adhere to medication twice than hypertensive patients with weak self-efficacy (aOR= 2.11; 95% CI = 1.27 to 3.52; p <0.004).Conclusion: Social support and self-efficacy improve medication adherence in hypertensive patients. Keywords: social support, self-efficacy, social cognitive theory, hypertension, medication adherence Correspondence:Sukma. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: sukmadenny1402@gmail.com. Mobile: +6281254428800.